National science-policy dialogue platforms of Mali and Senegal developed and submitted US$ 11 million bankable CSA projects to the Green Climate Fund - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
After building the capacities of the CCAFS platform members to prioritize CSA options and operationalize science-policy dialogue platforms at the national and district levels, two bankable projects in Mali and Senegal totalizing US$ 11 million were developed and submitted to the Green Climate Fund (GCF) for funding.